QUESTIONNAIRE «TEACHER THROUGH THE EYES OF STUDENTS» AS A TOOL FOR IMPLEMENTATION OF EDUCATION QUALITY IN UNIVERSITIES - Kuprii, Tetiana (Educological discourse, 2020)
The article deals with the effectiveness of the questionnaire "Teacher through the eyes of students" and the practical implementation of the form as a tool for assessing the personal and professional qualities of teachers and their direct links with the student in the context of pedagogical, sociological, managerial dimensions and cross-cultural sociological research. Student evaluation is required to adjust actions in educational processes and to make changes to the organization’s management, educational programs, and learning technologies. The efficiency and effectiveness of the educational process in higher education depends crucially on two key people - the teacher and the student. Students are the main consumers of educational outcomes. Therefore, in order to determine the degree of student satisfaction, the quality of teaching and teaching methods and the correspondence of the real learning process to the expectations of students, teaching makes it possible to make adjustments to the content of the course, improve yourself as an author and improve the quality of the educational product provided, which will undoubtedly lead to improvement of the process , which both students and teachers are interested in. According to the university leadership, studies of this type will help to increase the effectiveness of teachers’ professional activity, stimulate cooperation between both sides of the educational process. Different approaches to the formation of questions of the questionnaire of world universities with emphasis on pedagogical skills, contact with the audience, students’ interest in subjects, relevance to future professional activity are revealed. The author of the research proposed his own questionnaire, tested in a pilot sociological research and theoretically useful for educators and the administrative corps, which will encourage the teacher to improve himself.